Advantages of fixed-time artificial insemination in beef cattle farming (Research, Society and Development, 2024)
The objective of this research is to present a study on fixed-time artificial insemination (TAI) for beef cattle. A descriptive, qualitative study of a narrative literature review was carried out. IATF is an assisted reproduction technique that has significantly improved reproductive management on farms, relying on physiological and endocrinological principles to increase reproductive efficiency and profitability. It allows all reproductively capable cows to be inseminated at the same time, without having to monitor estrus individually, resulting in a higher service rate and accelerated pregnancy. Increased productivity and profitability: with a higher pregnancy rate and a reduced calving interval, there is an increase in the number of calves produced per year, increasing the productivity of the herd and, consequently, the profitability of livestock farming. Finally, it is known that TAI can reduce the incidence of health problems associated with heat detection, such as uterine diseases and physical injuries. Furthermore, by allowing a more uniform calving interval, it can improve animal welfare by reducing stress caused by prolonged or irregular estrous cycles.